Benchmarking and Rating of Private Commercial Banks of Bangladesh Through CAMELS Components - Haq, A H M Ziaul; Nasrin, Hosnay (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
The banking sector of Bangladesh is becoming more complicated than before. Ensuring the financial stability of the economy, monitoring, supervision, and continuous performance evaluation of the banking sector are compulsory. The present study, therefore, is an attempt to evaluate and compare the performance of our banks. One of the most effective supervisory techniques, CAMELS rating system has been used to benchmark and rate the banks based on their performance. In this study, 21 private commercial banks (PCBs) have been chosen as samples to meet the purpose of the study. Data for analysis has been collected from the banks’ annual reports for the period of 2008 to 2018. The result shows that none of the banks could achieve a ’strong’ position, and only SEBL was able to secure a ‘satisfactory’ mark. Unfortunately, AB bank was rated "marginal" in the composite rating, which is the lowest rating among the sample banks. Hence, AB bank needs to develop reform and follow-up programs as soon as possible to avoid financial failure.